Intrarenal dopaminergic system regulates renin expression - Zhang, Ming-Zhi (2009)
Dopamine is a major regulator of proximal tubule salt reabsorption and is a modulator of renin release. Dopamine has been reported to stimulate renin release in vitro through activation of D1-like receptors. However, previous studies investigating dopamine regulation of renin release in vivo have provided contradictory results, indicating stimulation, inhibition or no effect. We have previously reported that macula densa cyclooxygenase-2 (COX-2) is suppressed by dopamine. Since macula densa COX-2 stimulates renal renin expression, our current studies investigated dopamine regulation of renal renin release and synthesis in vivo. Acute treatment with a D1-like receptor agonist, fenoldopam, significantly inhibited renin release, as did acute inhibition of proximal tubule salt reabsorption with acetazolamide. In catechol-O-methyl transferase knockout (COMT-/-) mice, which have increased kidney dopamine levels due to deletion of the major intrarenal dopamine metabolizing enzyme, there was attenuation in response to a low salt diet of the increases of renal cortical COX-2 and renin expression and renin release. A high salt diet led to significant decreases in renal renin expression, but much less significant decreases in COMT-/- mice than wild type mice, resulting in higher renal renin expression in COMT-/- mice. In high salt treated wild type mice or COX-2 knockout mice on a normal salt diet, fenoldopam stimulated renal renin expression. These results suggest that dopamine predominantly inhibits renal renin expression and release by inhibiting macula densa COX-2, but suppression of renal cortical COX-2 activity reveals a contrasting effect of dopamine to stimulate renal renin expression through activation of D1-like receptors.